Dynamics of Structures in SI Units - Chopra, Anil K. (Pearson International Content, 2024)
Dynamics of Structures introduces the theory of structural dynamics and its application to earthquake analysis, response, design and evaluation of structures. Expert Anil K. Chopra presents this often difficult subject as simply as possible. No prior knowledge of structural dynamics is assumed, and the presentation is detailed enough for self-study. Analytical procedures summarize key steps, making them easy for you to replicate. Worked-out examples, illustrative figures and real photos help you gain a deeper understanding of how theory is applied to practical problems. The 6th Edition includes a new chapter on dynamics of building-soil interaction. Updates and revisions throughout reflect current building codes, methods and research.